Silica hydrogel with high water content and high oxygen permeability, contact lens and preparation method of contact lens

By adopting a high-water and high-oxygen permeability silicone hydrogel formula, the wearing discomfort caused by low moisture content of silicone hydrogel lenses is solved, and the high oxygen permeability and comfort of the lenses are achieved, which extends the service life and improves the overall performance of the lenses.

CN119591809APending Publication Date: 2025-03-11GANSU TIANHOU OPTICAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411891234.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Due to the low moisture content of existing silicon hydrogel lenses, the surface hydrophilicity is not good enough, which affects the wearing effect, such as dry eyes and low comfort.

Method used

Silicon hydrogel lenses with high oxygen permeability and high moisture content are prepared by mixing the silicone-containing monomer mixture with hydrophilic monomers, crosslinking agents, initiators and solvents in a specific proportion, and polymerization and curing by ultrasonic dissolution and heat-induced polymerization and curing.

Benefits of technology

It improves the oxygen permeability and comfort of the lens, reduces protein and lipid precipitation, extends the service life of the lens, and enhances the tensile strength and moisturizing properties of the lens.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a silicon hydrogel with high water content and high oxygen permeability, a contact lens and a preparation method of the contact lens, and the silicon hydrogel with high water content and high oxygen permeability is prepared by polymerization reaction of the following components by mass: 20-60% of a silicon-containing monomer mixture; 20-50% of a hydrophilic monomer; 0.1 to 4% of a cross-linking agent; 0.2 to 5% of an initiator; and 10-30% of a solvent. In the formula of the silicone hydrogel, the compatibility of p-vinylphenyltris (trimethylsiloxy) silane (TTMS) and a hydrophilic monomer can be improved, the problem that the solubility of a silicon-containing monomer and the hydrophilic monomer is poor is solved, and the water content of the lens is improved; and furthermore, due to combination with 3-acrylamidopropyl tri (trimethylsiloxy) silane, prolonged release of oxygen can be promoted, and the oxygen conveying capability of the lens is improved, so that the oxygen permeability of the lens is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of silicone hydrogels, and in particular to a silicone hydrogel with high water content and high oxygen permeability and a contact lens prepared by using the silicone hydrogel. The present invention also relates to a method for preparing the contact lens. Background Art

[0002] The materials used to prepare contact lenses are usually divided into hydrogels and silicone hydrogels. Since hydrogel lenses are prone to accumulating protein precipitation, they need to be cleaned and replaced regularly to maintain the clarity and comfort of the lenses. In addition, the oxygen permeability of hydrogel lenses is relatively low, and the oxygen permeability is limited by the water content. Long-term wearing may cause dry eyes, and the water in lenses with high water content is easy to evaporate, which will also cause dry eyes. Lenses made of silicone hydrogel have high oxygen permeability, long-term wearing comfort, and greatly reduce protein and lipid precipitation, improving the clarity and service life of the lenses. This anti-precipitation performance ensures the transparency and visual effect of the lenses, reduces eye irritation and the risk of eye infection, and makes the lenses have good softness and elasticity. For people with particularly sensitive eyes, this material can provide better comfort, making the lenses more widely accepted, and therefore more and more popular with consumers. However, due to the limitation of its own water content, silicone hydrogel has poor surface hydrophilicity, which affects the wearing effect, such as dry eyes, low comfort and other problems. Summary of the invention

[0003] One of the purposes of the present invention is to provide a high-water-content, high-oxygen-permeable silicone hydrogel to solve the technical problem that the existing silicone hydrogel has low water content and affects the wearing effect.

[0004] The second object of the present invention is to provide a contact lens made of the above-mentioned high water content and high oxygen permeability silicone hydrogel.

[0005] The third object of the present invention is to provide a method for preparing the above-mentioned contact lens.

[0006] To achieve its purpose, the present invention adopts the following technical solution: A high water content and high oxygen permeability silicone hydrogel, characterized in that, in terms of mass percentage, the silicone hydrogel is formed by polymerization reaction of the following components: Silicon-containing monomer mixture: 20-60%; Hydrophilic monomer: 20-50%; Cross-linking agent: 0.1-4%; Initiator: 0.2-5%; Solvent: 10-30%; The silicon-containing monomer mixture is a mixture of 3-acrylamidopropyl tris(trimethylsiloxy)silane (TMSAA) and p-vinylphenyl tris(trimethylsiloxy)silane (TTMS); Or: the silicon-containing monomer is a mixture of one or more of 3-acrylamidopropyl tris(trimethylsiloxy)silane (TMSAA) or p-vinylphenyl tris(trimethylsiloxy)silane (TTMS) and 1,3-bis(3-methacryloxypropyl)tetrakis(trimethylsiloxy)disiloxane, (3-methacryloxy-2-hydroxypropoxy)propylbis(trimethylsiloxy)methylsilane (SIGMA) or terminal acryloxy ethylene oxide-dimethylsiloxane-ethylene oxide Aba block copolymer, 80-120 Cst (DBE-U12).

[0007] As a preferred embodiment of the technical solution of the present invention, the hydrophilic monomer is one or more of hydroxyethyl methacrylate (HEMA), methacrylic acid (MA), N-vinyl pyrrolidone (NVP), 2-methacryloyloxyethyl phosphorylcholine (MPC), and N,N-dimethylacrylamide (DMAA).

[0008] Furthermore, the cross-linking agent is one or more of ethylene glycol dimethacrylate (EGDMA), tripropylene glycol diacrylate, and trimethylolpropane trimethacrylate (TMPTMA).

[0009] Furthermore, the initiator is one of azobisisobutyronitrile and benzoyl peroxide, or a mixture of both.

[0010] Furthermore, the solvent is one or a mixture of n-butanol, tert-amyl alcohol or isopropanol.

[0011] The above-mentioned high water content and high oxygen permeability silicone hydrogel can be used to make contact lenses, and the preparation method is as follows: Weigh each component according to the formula, first add the silicon-containing monomer mixture into the solvent and ultrasonically dissolve it to obtain a silicon-containing monomer solution, then add the hydrophilic monomer, cross-linking agent, and initiator into the silicon-containing monomer solution, stir evenly and inject into the silicone hydrogel mold, and use thermal initiation polymerization to cure. Finally, place the mold containing the sample in an ethanol solution and soak it for 0.4-4h, take it out, and soak it in purified water for 30-40min, until all the residual ethanol on the lens surface is removed, so as to obtain a silicone hydrogel lens.

[0012] Furthermore, the ultrasonic dissolution time is 10-30 min.

[0013] Furthermore, the curing temperature is 90-120° C. and the curing time is 40-70 minutes.

[0014] Furthermore, the volume fraction of the ethanol solution is 10-50%.

[0015] Compared with the prior art, the silicone hydrogel formula and silicone hydrogel lens provided by this solution have the characteristics of high transparency, high water content, high oxygen permeability, slow water loss, high tensile strength, etc.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The p-vinylphenyl tris(trimethylsiloxy)silane (TTMS) in the silicone hydrogel formula of the present invention can improve the compatibility with the hydrophilic monomer, solve the problem of poor solubility of silicon-containing monomers and hydrophilic monomers, and improve the water content of the lens; further, it is combined with 3-acrylamidopropyl tris(trimethylsiloxy)silane to promote the prolonged release of oxygen, improve the ability of the lens to transport oxygen, and thus improve the oxygen permeability of the lens.

[0017] 2. The preparation process of conventional contact lenses is to add all the components and then mix them. The silicon material is prone to agglomeration due to its slow dissolution rate, which affects the appearance and homogeneity of the contact lenses. To solve this technical problem, the present invention first dissolves the silicon-containing monomer mixture in a solvent and then adds other components. Firstly, the dissolution rate of the silicon material can be increased, thereby improving the overall solubility of the system. Secondly, it helps to evenly disperse the silicon monomer in the solution, thereby avoiding agglomeration and improving the quality and performance of the final product.

[0018] 3. The present invention first soaks the components of the silicone hydrogel formula in an ethanol solution and then in purified water after thermal polymerization. The purpose is to first use the solubility and volatility of ethanol to clean the precipitate on the surface of the lens, and then soak it in purified water to balance the lens, remove the residual ethanol on the surface of the lens, and restore the wet state of the lens. There are fewer impurities in purified water, which can avoid secondary contamination of the lens. At the same time, purified water can help the lens reabsorb moisture and restore its original state, ensuring the comfort and oxygen permeability of the lens.

[0019] In summary, the silicone hydrogel provided by the present invention has a high water content and is more transparent. The silicone hydrogel contact lenses made of the silicone hydrogel have high oxygen permeability, making them more comfortable to wear. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1-9 The oxygen permeability test diagrams of Examples 1-5 and Comparative Examples 1-4 are shown in sequence; Figure 10-18 The transmittance detection diagrams of Examples 1-5 and Comparative Examples 1-4 are shown in order. DETAILED DESCRIPTION

[0021] The following is a detailed description of the preparation method of the high water content, high oxygen permeability silicone hydrogel, contact lens and angle contact lens of the present invention through specific examples.

[0022] Example 1 In this embodiment, the high water content and high oxygen permeability silicone hydrogel is prepared by mixing 15 g of 1,3-bis(3-methacryloxypropyl)tetrakis(trimethylsiloxy)disiloxane, 10 g of p-vinylphenyl tris(trimethylsiloxy)silane (TTMS), 9 g of terminal propyleneoxy ethylene oxide-dimethylsiloxane-ethylene oxide Aba block copolymer, 80-120 Cst, and 2 g of 3-acrylamidopropyl tris(trimethylsiloxy)silane (TMSAA), adding 15 g of n-butanol, and ultrasonically dissolving for 10 min to obtain a silicone monomer mixture, and then adding 30 g of N-vinyl pyrrolidone and 8 g of Hydroxyethyl methacrylate, 0.25g ethylene glycol dimethacrylate (EGDMA), and 0.3g azobisisobutyronitrile are stirred for 0.6h to mix evenly, and cured by thermal polymerization at a temperature of 120°C for 45min. After the reaction is completed, the mold containing the sample is immersed in a 20% by volume ethanol solution for 1.5h, and the sample is obtained after demolding; then, the sample is immersed in purified water for 20min, taken out, and the soaking process in purified water is repeated 3 times, and finally taken out to obtain the silicone hydrogel contact lens.

[0023] Example 2 In this embodiment, the high water content and high oxygen permeability silicone hydrogel is prepared by mixing 25g of 1,3-bis(3-methacryloxypropyl)tetrakis(trimethylsiloxy)disiloxane and 8g of 3-acrylamidopropyltris(trimethylsiloxy)silane (TMSAA), adding 15g of n-butanol, and ultrasonically dissolving for 20 minutes to obtain a silicone monomer mixture, then adding 30g of N-vinyl pyrrolidone, 6g of hydroxyethyl methacrylate, 0.25g of ethylene glycol dimethacrylate (EGDMA), and 0.3g of azobisisobutyronitrile, stirring for 0.8h to mix evenly, and curing by thermal initiation polymerization at a curing temperature of 110°C and a curing time of 60min. After the reaction is completed, the mold containing the sample is immersed in a 30% by volume ethanol solution for 40min, and the sample is demolded to obtain the sample; then, the sample is immersed in purified water for 20min, taken out, and the soaking process in purified water is repeated 3 times, and finally taken out to obtain the silicone hydrogel contact lens.

[0024] Example 3 In this embodiment, the high water content and high oxygen permeability silicone hydrogel is prepared by mixing 20g of 1,3-bis(3-methacryloxypropyl)tetrakis(trimethylsiloxy)disiloxane and 15g of p-vinylphenyltris(trimethylsiloxy)silane (TTMS), adding 15g of n-butanol, and ultrasonically dissolving for 20 minutes to obtain a silicone monomer mixture, then adding 30g of N-vinylpyrrolidone, 8g of hydroxyethyl methacrylate, 0.25g of ethylene glycol dimethacrylate (EGDMA), and 0.3g of azobisisobutyronitrile, stirring for 1 hour to mix evenly, and curing by thermal initiation polymerization at a curing temperature of 100°C and a time of 60 minutes. After the reaction is completed, the mold containing the sample is immersed in a 20% by volume ethanol solution for 1 hour, and the sample is demolded to obtain the sample; then, the sample is immersed in purified water for 20 minutes, taken out, and the soaking process in purified water is repeated 3 times, and finally taken out to obtain the silicone hydrogel contact lens.

[0025] Example 4 In this embodiment, the high water content and high oxygen permeability silicone hydrogel is prepared by mixing 15 g of 1,3-bis(3-methacryloxypropyl)tetrakis(trimethylsiloxy)disiloxane, 10 g of p-vinylphenyl tris(trimethylsiloxy)silane (TTMS), and 5 g of (3-methacryloxy-2-hydroxypropoxy)propylbis(trimethylsiloxy)methylsilane (SIGMA), adding 15 g of n-butanol, and ultrasonically dissolving for 10 min to obtain a silicone monomer mixture, and then adding 25 g of N-vinyl pyrrolidone, 6 g hydroxyethyl methacrylate, 0.25 g ethylene glycol dimethacrylate (EGDMA), and 0.3 g azobisisobutyronitrile were stirred for 0.6 h to mix evenly, and cured by thermal polymerization at a temperature of 110° C. for 50 min. After the reaction was completed, the mold containing the sample was immersed in a 30% by volume ethanol solution for 1 h, and the sample was obtained after demolding; then, the sample was immersed in purified water for 20 min, taken out, and the soaking process in purified water was repeated 3 times, and finally taken out to obtain the silicone hydrogel contact lens.

[0026] Example 5 25g of 1,3-bis(3-methacryloxypropyl)tetrakis(trimethylsiloxy)disiloxane, 10g of p-vinylphenyltris(trimethylsiloxy)silane (TTMS), and 15g of n-butanol were mixed and dissolved by ultrasonic for 15 minutes, and then 30g of N-vinylpyrrolidone, 8g of hydroxyethyl methacrylate, 0.25g of ethylene glycol dimethacrylate (EGDMA), and 0.3g of azobisisobutyronitrile were added, mixed and stirred for 0.6-1h, and cured by thermal initiation at a temperature of 110°C for 60min. After the reaction was completed, the mold containing the sample was immersed in 20% alcohol for 1.5h, and the sample was obtained after demolding; then, the sample was immersed in purified water for 20min, taken out, and the soaking process in purified water was repeated 3 times, and finally taken out to obtain the silicone hydrogel contact lens.

[0027] In this embodiment, the high water content and high oxygen permeability silicone hydrogel is prepared by mixing 25g of 1,3-bis(3-methacryloxypropyl)tetrakis(trimethylsiloxy)disiloxane and 10g of p-vinylphenyltris(trimethylsiloxy)silane (TTMS), adding 15g of n-butanol, and ultrasonically dissolving for 15 minutes to obtain a silicone monomer mixture, then adding 30g of N-vinylpyrrolidone, 8g of hydroxyethyl methacrylate, 0.25g of ethylene glycol dimethacrylate (EGDMA), and 0.3g of azobisisobutyronitrile, stirring for 0.6h to mix evenly, and curing by thermal initiation polymerization at a curing temperature of 110°C and a curing time of 60min. After the reaction is completed, the mold containing the sample is immersed in a 20% by volume ethanol solution for 1.5h, and the sample is demolded to obtain the sample; then, the sample is immersed in purified water for 20min, taken out, and the soaking process in purified water is repeated 3 times, and finally taken out to obtain the silicone hydrogel contact lens.

[0028] Comparative Example 1: The other components, contents and parameters of Comparative Example 1 are the same as those of Example 1, except that 3-acrylamidopropyl tris(trimethylsiloxy)silane (TMSAA) is not added in Comparative Example 1; Comparative Example 2: Comparative Example 2 is the same as Example 1 in other components, contents and parameters, except that p-vinylphenyl tris(trimethylsiloxy)silane (TTMS) is not added in Comparative Example 1; Comparative Example 3: Comparative Example 3 and Example 1 have the same other components, contents and parameters, except that in Comparative Example 3, the addition ratio of p-vinylphenyl tris(trimethylsiloxy)silane (TTMS) is reduced to 1.0 g.

[0029] Comparative Example 4: Comparative Example 34 is the same as Example 1 in other components, contents and parameters, except that the addition ratio of 16 g of p-vinylphenyl tris(trimethylsiloxy)silane (TTMS) in Comparative Example 3 is reduced to 5 g.

[0030] The contact lenses obtained in the above Examples 1-5 and Comparative Examples 1-4 were subjected to performance and tensile tests, and the results are as follows.

[0031] 1. Performance Testing 1. Detect the oxygen permeability of contact lenses: Use an oxygen permeability tester to measure the oxygen permeability of contact lenses. The experimental results are shown in Figure 1-9 ; 2. Detect the water content of contact lenses: Use the drying method to detect the water content of the lenses.

[0032] 3. Test the light transmittance of contact lenses: Use the TM-8S lens transmittance tester to test the light transmittance performance of contact lenses. The experimental results are shown in 10-18; 4. Detect the water loss rate of the lens: Use the QL-100B fast halogen moisture tester to measure the moisturizing performance of contact lenses.

[0033] The test results of the silicone hydrogel lenses of Examples 1-5 and Comparative Examples 1-3 are shown in Table 1.

[0034] Table 1 Performance test results of silicone hydrogel lenses prepared in Examples 1-5 and Comparative Examples 1-4 It can be seen from the above data that the oxygen permeability of the lenses in Examples 1-5 of the present invention is significantly higher than that in Comparative Examples 1-4, while the water loss rate is lower than that in the Comparative Examples, indicating that the newly introduced silicon material components TTMS and TMSAA, combined with other silicon materials, can improve the oxygen permeability of the lenses to a certain extent, and as the added concentration increases, the oxygen permeability gradually increases, and at the same time, the water loss rate of the lenses can be reduced, thereby improving the moisturizing effect of the lenses.

[0035] 2. Lens stretching test Tensile tests are used to measure the tensile strength and ductility of contact lens materials to ensure that the lenses can withstand the mechanical stress of daily use and are not prone to cracking or deformation.

[0036] The elasticity and stability of the silicone hydrogel contact lens material were evaluated by the above method, and the results are recorded in Table 2.

[0037] Table 2 Tensile test results of silicone hydrogel lenses prepared in Examples 1-5 and Comparative Examples 1-4 It can be seen from the above data that the tensile strength of the lenses in Examples 1-5 is significantly higher than that in Comparative Examples 1-4, indicating that the newly introduced silicon material components TTMS and TMSAA, combined with other silicon materials, can improve the tensile strength of the lenses to a certain extent.

Claims

1. A high water content, high oxygen permeability silicone hydrogel, characterized in that: In terms of mass percentage, the silicone hydrogel is formed by polymerization of the following components: Silicon-containing monomer mixture: 20-60%; Hydrophilic monomer: 20-50%; Cross-linking agent: 0.1-4%; Initiator: 0.2-5%; Solvent: 10-30%; The silicon-containing monomer mixture is a mixture of 3-acrylamidopropyl tris(trimethylsiloxy)silane (TMSAA) and p-vinylphenyl tris(trimethylsiloxy)silane (TTMS); Or: the silicon-containing monomer is a mixture of one or more of 3-acrylamidopropyl tris(trimethylsiloxy)silane (TMSAA) or p-vinylphenyl tris(trimethylsiloxy)silane (TTMS) and 1,3-bis(3-methacryloxypropyl)tetrakis(trimethylsiloxy)disiloxane, (3-methacryloxy-2-hydroxypropoxy)propylbis(trimethylsiloxy)methylsilane (SIGMA) or terminal acryloxy ethylene oxide-dimethylsiloxane-ethylene oxide Aba block copolymer, 80-120 Cst (DBE-U12).

2. A high water content, high oxygen permeability silicone hydrogel as claimed in claim 1, characterized in that: The hydrophilic monomer is one or more of hydroxyethyl methacrylate (HEMA), methacrylic acid (MA), N-vinyl pyrrolidone (NVP), 2-methacryloyloxyethyl phosphorylcholine (MPC), and N,N-dimethylacrylamide (DMAA).

3. The high water content and high oxygen permeability silicone hydrogel according to claim 1, characterized in that: The crosslinking agent is one or more of ethylene glycol dimethacrylate (EGDMA), tripropylene glycol diacrylate, and trimethylolpropane trimethacrylate (TMPTMA).

4. The high water content and high oxygen permeability silicone hydrogel according to claim 1, characterized in that: The initiator is one of azobisisobutyronitrile and benzoyl peroxide or a mixture of the two.

5. The high water content and high oxygen permeability silicone hydrogel according to claim 1, characterized in that: The solvent is one or a mixture of n-butanol, tert-amyl alcohol or isopropanol.

6. Contact lenses made of the high water content and high oxygen permeability silicone hydrogel according to any one of claims 1 to 5.

7. A method for preparing a highly water-containing, highly oxygen-permeable silicone hydrogel contact lens as claimed in claim 6, characterized in that: Weigh each component according to the formula, first add the silicon-containing monomer mixture into the solvent and ultrasonically dissolve it to obtain a silicon-containing monomer solution, then add the hydrophilic monomer, cross-linking agent, and initiator into the silicon-containing monomer solution, stir evenly and inject into the silicone hydrogel mold, and use thermal initiation polymerization to cure. Finally, place the mold containing the sample in an ethanol solution and soak it for 0.4-4h, take it out, and soak it in purified water for 30-40min, until all the residual ethanol on the lens surface is removed, so as to obtain a silicone hydrogel lens.

8. The method for preparing a highly water-containing, highly oxygen-permeable silicone hydrogel contact lens according to claim 7, characterized in that: The ultrasonic dissolution time is 10-30 min.

9. The method for preparing a highly water-containing, highly oxygen-permeable silicone hydrogel contact lens according to claim 8, characterized in that: The curing temperature is 90-120° C. and the curing time is 40-70 minutes.

10. The method for preparing a highly water-containing, highly oxygen-permeable silicone hydrogel contact lens according to claim 8, characterized in that: The volume fraction of the ethanol solution is 10-50%.